RESISTANT STARCH PRODUCTION TECHNOLOGIES – A REVIEW - Raigond, Pinky; Ezekiel, Rajarathnam; Singh, Brajesh; Dutt, Som; Joshi, Alka; Rinki, Rinki (Potato Journal, 2016)
Due to increasing health awareness among consumers; food manufacturers, researchers and producers are aiming to develop functional foods with additional health benefits along with providing basic nutrition. Glycemic index of food directly affects the blood sugar level and caused fatal health problems such as diabetes and obesity. Glycemic index of a food is inversely related to its resistant starch content, hence, food nutritionists are looking out for incorporation of resistant starch as a functional ingredient in processed foods to increase its acceptability in terms of healthy alternative. Resistant starch is gaining attention as functional ingredient due to its unique physiochemical and functional properties. Incorporation of resistant starch (RS) in wide variety of products such as breads, cookies, muffins, pizza crust, tortillas, breakfast cereals and snack products are already being practiced. Production of RS at commercial level requires industrial inventions required to meet the growing demand of it as a functional ingredient. Various techniques such as heat, enzymatic, heat with enzyme and chemical treatments are being practiced for production of resistant starch. The RS products namely, Hi maize, CrystaLean, Novelose 240, Novelose 260, Novelose 300, C*Actistar, FibersymTM HA, FibersymTM 80ST, Nutriose FB, Fibersol 2, HylonR VII and Neo –amylose are available in market. These products are different forms of RS such as RS-2, RS-3 and RS-4, contain different concentrations of dietary fibres. This review covers the various techniques being followed for the production of resistant starch.